2020
DOI: 10.21203/rs.3.rs-16202/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurological outcome after extracorporeal cardiopulmonary resuscitation for in-hospital cardiac arrest: a systematic review and meta-analysis

Abstract: BackgroundIn hospital cardiac arrest (IHCA) is a major adverse event with a high mortality rate if not treated appropriately. Extracorporeal cardiopulmonary resuscitation (ECPR), as adjunct to conventional cardiopulmonary resuscitation (CCPR) is a promising technique for IHCA treatment. Evidence pertaining to neurological outcomes after ECPR is still scarce. MethodsWe performed a comprehensive systematic search of all studies up to December 20th 2019. Our primary outcome was neurological outcome after ECPR at … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Neurologic outcome after ECPR was analyzed in a systematic review and meta-analysis by Gravesteijn et al who identified 19 studies where neurologic outcome was assessed using the CPC score (8). They found that in survivors, the proportion of favorable neurologic outcome (CPC of 1-2) was high (84%) with a low study heterogeneity (I 2 ¼ 24%, P ¼ 0.90).…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic outcome after ECPR was analyzed in a systematic review and meta-analysis by Gravesteijn et al who identified 19 studies where neurologic outcome was assessed using the CPC score (8). They found that in survivors, the proportion of favorable neurologic outcome (CPC of 1-2) was high (84%) with a low study heterogeneity (I 2 ¼ 24%, P ¼ 0.90).…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have compared ECPR with CCPR and suggested that ECPR might be associated with improved survival to discharge or neurological outcomes. (23)(24)(25)(26)(27) However, all systematic reviews have rated the quality of evidence as low, with risk of bias. A recent systematic review by Holmberg et al for the International Liaison Committee on Resuscitation's Advanced Life Support and Paediatric Task Forces demonstrated mixed results.…”
Section: Ecpr Versus Ccpr In Adult Ohcamentioning
confidence: 99%